Figurative Language Used In The Browning's Poems - Nisa, Atik Choirun; , Dr. Maryadi, M.A (ATIK CHOIRUN NISA, 2016)
This research has two major objectives proposed by the researcher, they are (1) to identify the types of figurative language used in The Browning's poems, (2) to find out the implied meaning of figurative language used in The Browning's poems. The type of this research is descriptive qualitative. The data source of this research is taken from the poems by The Browning. Regarding with the method of collecting the data, the researcher applies observation and documentation by studying deeply on the poems by The Browning and then the researcher clarifies the data using Perrine Lawrence's theory of figurative language and other scientists that support it. Whilst regarding the implied meaning of the figurative language used in The Browning's poems, the reasearcher uses the theory of Leech of types of meanings and other scientists' theories that support it.The result of the study indicates that in The Browning's poems, there are ten types of figurative language used namely; Symbol, Simile, Metaphor, Synecdoche, Paradox, Metonymy, Personification, Apostrophe, Hyperbole, and Understatement. Closerly related to the implied meanings of figurative language used in the poems, the researcher here finds five types of implied meanings namely; connotative, affective, stylistic, conceptual, and reflective meaning.